Peran Permainan Tradisional Lompat Tali dalam Menstimulasi Perkembangan Motorik Kasar Anak Usia Dini - Riyanti Latama; Lisnawaty Atuna; Siti Nur Afni Kantoli; Raihan Abaidata; Cika Aprilia Kuku; Mita Sari (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This study aims to examine the role of the traditional rope jumping game in stimulating the development of gross motor skills and social skills of early childhood at Kiddi Care Kindergarten. The method used is descriptive qualitative, with data collection techniques through direct observation and interviews with accompanying teachers. The results of the observation indicate that the rope jumping game can enhance children's motor coordination, balance, agility, and muscle strength, which are crucial components of gross motor development. In addition, this game also strengthens children's abilities in concentration, discipline, and cooperation. Children appear enthusiastic, can follow the rules, and show positive social interactions during the activity. Interviews with teachers support these findings, where teachers state that the rope jumping game is an effective means of training physical skills while shaping children's character. Based on these results, it can be concluded that the traditional rope jumping game is a worthy addition to early childhood learning as a fun and holistic educational medium.